Quality assurance - Long, David (Henry Stewart Talks, 2012)
GLP as a quality assurance system, OECD GLP principles, Quality assurance program implementation, Independent monitoring, Programme of audits/inspections, Audit personnel Recording and documentation, Study director audit responsibilities, Typical QA inspection report, QA personnel, QA audits/inspections types, QA statement, QA responsibilities